Effects of Continuous Nitrogen Fertilizer Application on the Diversity and Composition of Rhizosphere Soil Bacteria - Ren, Ning; Wang, Yang; Ye, Youliang; Zhao, Yanan; Huang, Yufang; Fu, Wen; Chu, Xv (Frontiers in Microbiology, 2020)
Little has been reported on the effects of long-term fertilization on soil microbial diversity. Here, we investigated the effects of long-term continuous nitrogen (N) fertilization on the diversity and composition of soil bacteria, using data of a 10-year field experiment with five N application rates (0, 120, 180, 240, and 360 kg N hm-2). The results revealed varying degrees of reduction in the numbers of bacterial operational taxonomic units (OTUs) in response to different N application rates. The highest wheat yield and number of proprietary bacterial OTUs were found in the N input of 180 kg N hm-2. In terms of average relative richness, the top seven phyla of soil bacteria in the rhizosphere of wheat after long-term nitrogen application were Proteobacteria, Actinobacteria, Acidobacteria, Chloroflexi, Bacteroidetes, Gemmatimonadetes, and Patescibacteria. Among these, Proteobacteria and Gemmatimonadetes were found to be unaffected by nitrogen fertilizer and soil environmental factors (pH, C:N ratio, and NO3- concentration), whereas Acidobacteria and Actinobacteria showed significant positive and negative correlations, respectively with soil pH. The richness of Actinobacteria significant increased in the N180 treatment. Patescibacteria and Bacteroidetes showed significant positive correlations with soil NO3- and wheat yield, and the average relative richness of these two phyla was high under long-term application of the N180 treatment. These findings indicate that the relative richness of Patescibacteria and Bacteroidetes can affect wheat yield. In conclusion, the results of our 10-year field experiments clearly show that long-term N fertilization can significantly affect most of the dominant soil bacterial species via changing soil pH. The richness of Actinobacteria can serve as an indicator of decreased soil pH caused by long-term N fertilization.